Floral biology and breeding system of three Ipomoea weeds - Maimoni-Rodella,R.C.S. (2007)
The floral biology of three weeds, Ipomoea cairica, I. grandifolia and I. nil (Convolvulaceae), was studied in Botucatu and Jaboticabal, São Paulo, in southeastern Brazil. The three species are melittophilous, with a varied set of floral visitors, but with some overlapping. Cluster analysis using Jacquard similarity index indicated a greater similarity among different plant species in the same locality than among the populations at different places, in relation to floral visitor sets. The promiscuous and opportunistic features of the flowers were shown, with such type of adaptation to pollination being advantageous to weeds since pollinator availability is unpredictable at ruderal environments.